Evaluating Glycerol’s Performance as a Sustainable Dehydrator in Ethanol Purification - Muhali, Muhali; Hulyadi, Hulyadi; Bayani, Faizul (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This research aims to evaluate the effectiveness of glycerol as a dehydrator in the process of purifying ethanol solutions. This study is a quantitative descriptive research aimed at analyzing the effectiveness of glycerol, derived from used cooking oil, as a water dehydrating agent in the ethanol purification process. Data obtained will be quantitative and statistically analyzed to evaluate glycerol’s performance as a dehydrator. The research was conducted at the Chemistry Laboratory of Mandalika Education University (UNDIKMA) over a specific period according to the research schedule.Independent Variable is glycerol from used cooking oil as a dehydrating agent. The concentration of glycerol used is determined based on the percentage of glycerol in the ethanol solution. Dependent variable the effectiveness of ethanol purification, measured through the comparison of density and percentage of standard bioethanol and Controlled variables is Temperature and pressure during the dehydration process, duration of the purification process, and the initial ethanol concentration before purification. Data analysis uses a simple regression curve that follows Lambert Beer’s law. In conclusion, the results obtained (increasing the ethanol concentration to 90.5%) show that glycerol is a very effective dehydrator in reducing water content, especially for solutions with high water content such as ethanol at an initial concentration of 23.3%.